ANALISIS KAUSALITAS ANTARA FDI DAN PERTUMBUHAN EKONOMI DI ASEAN - Herlina Adelia Manullang; Paidi Hidayat (Departemen Ekonomi Pembangunan USU, 2014)
he aim of the study is to analyze the relationship between the variables FDI and economic growth in ASEAN member countries, especially Indonesia, Malaysia, Philippines, Singapore and Thailand. Data used in this study is the time series of the year 1981-2012 were obtained from the quantitative world bank’s official website. Method of testing is done using Unit Root Test, Johansen Cointegration Test, VAR, VECM, and Granger Causality. Result of the study concluded that there is a long-term relationship between FDI and economic growth in Indonesia, Malaysia, Philippines, and Singapore. There is a one-way relationship between the variables FDI and economic growth in Indonesia and Singapore. Economic growth affects FDI in Indonesia, otherwise FDI affects economic growth in Singapore. While in Malaysia, Philippines, and Thailand there is no causality between FDI and growth.Keywords : Unit Root Test, Johansen Cointegration Test, VAR, VECM, and Granger Causality.